2009
DOI: 10.1128/iai.01218-08
|View full text |Cite
|
Sign up to set email alerts
|

ace , Which Encodes an Adhesin in Enterococcus faecalis , Is Regulated by Ers and Is Involved in Virulence

Abstract: Enterococcus faecalis is an opportunistic pathogen that causes numerous infectious diseases in humans and is a major agent of nosocomial infections. In this work, we showed that the recently identified transcriptional regulator Ers (PrfA like), known to be involved in the cellular metabolism and the virulence of E. faecalis, acts as a repressor of ace, which encodes a collagen-binding protein. We characterized the promoter region of ace, and transcriptional analysis by reverse transcription-quantitative PCR an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
121
1
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(128 citation statements)
references
References 36 publications
4
121
1
2
Order By: Relevance
“…It is possible that CspR may be one of the 'moonlighting' protein group, meaning that it can have two unrelated functions according to its intra-or extracellular location. To date, for the prevention of E. faecalis infections, in addition to lipoteichoic acid and capsular polysaccharides, three proteins known as virulence factors have been proposed as possible immunotherapy targets: the general stress protein Gls24, the collagen adhesion Ace, and the endocarditis-and biofilm-associated pilus Ebp (Giard et al, 2000;Huebner et al, 2000;Lebreton et al, 2009;Murray, 1990;Singh & Murray, 2012;Singh et al, 2007;Teng et al, 2005). Our results showed that a cold-shock RNA-binding protein can present a double localization, both intercellularly and at the surface of the bacteria, and that anti-CspR antibody protects insect larvae against infection by E. faecalis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is possible that CspR may be one of the 'moonlighting' protein group, meaning that it can have two unrelated functions according to its intra-or extracellular location. To date, for the prevention of E. faecalis infections, in addition to lipoteichoic acid and capsular polysaccharides, three proteins known as virulence factors have been proposed as possible immunotherapy targets: the general stress protein Gls24, the collagen adhesion Ace, and the endocarditis-and biofilm-associated pilus Ebp (Giard et al, 2000;Huebner et al, 2000;Lebreton et al, 2009;Murray, 1990;Singh & Murray, 2012;Singh et al, 2007;Teng et al, 2005). Our results showed that a cold-shock RNA-binding protein can present a double localization, both intercellularly and at the surface of the bacteria, and that anti-CspR antibody protects insect larvae against infection by E. faecalis.…”
Section: Discussionmentioning
confidence: 99%
“…mellonella infection experiments. Infection of G. mellonella larvae with E. faecalis was accomplished as previously described by Lebreton et al (2009). Briefly, using a syringe pump (KD Scientific), larvae (about 0.3 g and 3 cm long) were infected subcutaneously with washed E. faecalis WT, DcspR and corresponding complemented strains from an overnight culture in GM17, with 6610 6 ± 0.6610 6 c.f.u.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Microbiología proteína de superfi cie extracelular (Esp), la cual promueve la adhesión, colonización y evasión del sistema inmune, también participa en la generación de biopelícula y aparentemente cumple un rol en la resistencia antimicrobiana; citolisina (Cyl), también denominada hemolisina, que posee propiedades β-hemolíticas en humanos y es bactericida contra bacterias grampositivas; gelatinasa (Gel) que provee de nutrientes a la bacteria degradando el tejido del hospedero y además presenta algún tipo de función en la formación de biopelícula; hialuronidasa que actúa despolimerizando la molécula de mucopolisacárido del tejido conectivo lo que facilita la diseminación de la bacteria; determinantes de feromonas (Eep) son capaces de modular de modo importante la respuesta infl amatoria in vivo; antígeno A (EfaA) que se asocia a la adherencia de la bacteria tanto a células bióticas y superfi cies abióticas, además de participar en ciertas etapas de la formación de biopelícula; proteína de superfi cie celular (Ace) que exhibe una fuerte similitud con la proteína del mismo nombre producida por Staphylococcus aureus, la cual posee la capacidad de unirse al colágeno y presentaría un rol en la patogénesis de la endocarditis 12 ; sustancia de agregación (Agg) que actúa mediando la unión específi ca de la bacteria al epitelio intestinal, células del epitelio renal, neutrófi los humanos y macrófagos además de aumentar la internalización y vida intracelular del microorganismo 13 . La presencia de un pilus de E. faecalis es importante en la producción de la biopelícula, la cual se sustenta en la proteína Bps.…”
Section: Artículo Originalunclassified
“…Infection of Galleria mellonella larvae with E. faecalis was accomplished as previously described by Lebreton et al (2009). Briefly, using a syringe pump (KD Scientific), larvae (about 0.3 g and 3 cm in length) were infected subcutaneously with washed E. faecalis cells from an overnight culture in GM17, with 1.5610 6 ±0.15610 6 or 3610 6 ±0.3610 6 c.f.u.…”
Section: Rna Isolation and Quantitative Reverse Transcriptase Pcr (Rtmentioning
confidence: 99%